Psychometric Evaluation of the Major Depression Inventory (MDI) as a Depression Severity Scale in Chinese Patients With Coronary Artery Disease. Findings From the MEDEA FAR-EAST Study. - Chen, Yixiao; Fang, Xiaoyan; Shuai, Xueqian; Fritzsche, Kurt; Leonhart, Rainer; Hoschar, Sophia; Li, Li; Ladwig, Karl-Heinz; Ma, Wenlin; Wu, Heng (Frontiers in Psychiatry, 2019)
Background: It is highly recommended that all patients with coronary artery disease should be screened for depression. The Major Depression Inventory (MDI) is a widely used self-rating scale for the assessment of depression but is not valid in Chinese language. The present study was designed to assess the reliability and validity of a version of the MDI translated into Chinese among patients with acute myocardial infarction (AMI). Methods: Data were derived from the “Multicenter Delay in Patients Experiencing Acute Myocardial Infarction in Shanghai” (MEDEA FAR-EAST) study. Using a cross-sectional study design, the Chinese version of the MDI was administered to a total of 267 inpatients. The internal consistency reliability of the MDI scale was evaluated based on the Cronbach’s coefficient and the binary coefficient for the whole scale. Exploratory factor analysis was performed to assess the internal consistency of the MDI. To examine is discriminant validity, we analyzed the correlation of the MDI score with the General Anxiety Disorder-7 (GAD-7) and World Health Organization-5 Well-Being Index (WHO-5) scale scores. Results: The Chinese version of the MDI showed high reliability (Cronbach’s alpha=0.909, split-half reliability=0.866). We identified one factor that explained 52% of the variance, which indicated that the MDI has satisfactory structural validity. The correlations of the MDI scores with the GAD-7 scores (r=0.425) and the WHO-5 scores (r=-0.365) were moderate, suggesting that the MDI has acceptable discriminant validity. Conclusions: The MDI was proved to be a highly reliable and satisfactory valid diagnostic screening tool to assess depression in Chinese cardiac patients.